Formulation of emulsion of soybean (Glycinia soyae L.) tempeh and fermented spinach (Amaranthus sp.) using combination of gelatin and CMC as thickener - Agustine Susilowati; Aspiyanto Aspiyanto; Puspa Dewi Lotulung; Yati Maryati (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Mixture of soybean (Glycinia soyae L.) tempeh paste and spinach (Amaranthus sp.) fermented by Kombucha culture produces potential source of natural folic acid. The experiment activity aims to find out the best ratio of gelatin and CMC as thickener in emulsification to prepare supplement of natural folic acid. Emulsification process was conducted by adding gelatin and CMC at ratio of 0 : 0, 0.1 : 2, 0.2 : 4, 0.3 : 6, 0.4 : 8, and 0.5 : 10 (g/g) in mixture of fermented spinach concentration of 2.5, 5.0, 7.5, and 10.0% (w/w in soybean tempeh) and soybean tempeh. The best drying treatment was achieved at 50°C for 24 h. Result of experiment activity showed that based on the best folic acid, the optimum treatment to yield supplement paste was achieved at combination of gelatin-CMC ratio of 0.4 : 8 (g/100 g in mixture paste) and fermented spinach 2.5% (b/b in soybeans tempeh). Identification on folic acid in paste and supplement powder with mass spectra had been identified 6 folic acid monomer dominated by folic acid monomer with molecular weight (M+1) 442.87 and 442.66 Dalton (Da.) with relative intensity 100%. Paste and powder of supplement displayed distribution of particle size 1,745.1 and 984.1 nm with particle indexes of 1.124 and 1.121.Keywords : folic acid , gelatin, emulsification, tempeh, spinach, ratio.